Unusual ligand substitution of a metal–organic framework with distorted metal–ligand coordination. Issue 9 (10th February 2022) - Sakamoto, Hikaru; Ito, Akitaka; Ohtani, Masataka
Abstract : We demonstrate an unusual crystal-structure transition from metal–organic frameworks (MOFs) composed of ortho -phthalate ligands. Abstract : We demonstrate an unusual crystal-structure transition from metal–organic frameworks (MOFs) composed of ortho -phthalate ligands. The time-course change observed in X-ray diffraction experiments showed that the continuous structural transformation of MOFs occurs after immersion in N, N -dimethylformamide solution containing ortho - or para -tetrafluorophthalate ligands. Systematic study based on single crystal X-ray analysis reveals that the structural strain in the metal–ligand coordination network is a crucial factor in the potential of the metal center to undergo partial bond dissociation and ligand substitution.